An interactive Islamic mobile application for children - 'Hidup Cara Rasullullah' - Sarlan, A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Information and communication technology has enable education sector to evolve throughout the years. As trends of using portable devices are growing rapidly, the possibility to exploit them for the purpose of learning is immense. Malaysia is inhibited with 61.3 of Muslims. Therefore, informal learning in Islamic context for children is a vital part in any Muslim child development. However, the platform for children to obtain informal learning in Islamic Context is rarely seen. As such, this project will develop a mobile application for android that enables children at the age of four to six as well as their parents to learn about Islamic Hadiths in an interactive and engaging manner. Exploratory study is conducted to evaluate the process of learning Islamic contents for children, which will be the basic user requirements for the mobile application. Survey results shown the majority of Muslim parents provide their children with Islamic education at home through children's books, although the parents are in possession of a mobile device or tablet and have downloaded Islamic applications. Therefore, this project will develop an interactive mobile application called 'Hidup cara Rasulullah' to provide children a better understanding in the concept of Hadiths in daily lives. Â© 2016 IEEE.